Relativistic Spinning Particle without Grassmann Variables and the Dirac Equation - A. A. Deriglazov (Advances in Mathematical Physics)
We present the relativistic particle model without Grassmann variables which, being canonically quantized, leads to the Dirac equation. Classical dynamics of the model is in correspondence with the dynamics of mean values of the corresponding operators in the Dirac theory. Classical equations for the spin tensor are the same as those of the Barut-Zanghi model of spinning particle.